PENGARUH INVESTASI ASING DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BANTEN - Rahmatullah, Wahyu Nofaldo; Boedirochminarni, Arfida (Program Studi Ekonomi Pembangunan, 2024)
An important benchmark for achieving successful development can be seen from the level of economic growth at both the national and regional levels. The aim of the research is to identify the impact of foreign investment and population on economic growth in Banten Province as measured by Gross Regional Domestic Product. This research uses a quantitative descriptive approach where data is collected through the Central Statistics Agency for a time period starting from 2017 - 2022. The analysis technique used is panel regression analysis. The research results show that foreign investment and population have a positive and significant effect on Gross Regional Domestic Product in Banten Province